Congenital chylothorax: A series of eight cases - Jorge Antunes, Joana; Borges, Madalena; Mascarenhas, Andreia; Brito, Sara; Iglesias, Célia; Fernandes, Eduardo; Vieira, Eunice; Pinto, Filomena; Ferreira, Leonor; Tomé, Teresa; et al. (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
Introduction: Congenital chylothorax (CC) is the accumulation of lymph in the pleural space. The aim of this study was to review the cases of CC diagnosed in newborns admitted to a level III neonatal intensive care unit between January 2014 and December 2020. Results: Eight cases of CC were identified, all with prenatal diagnosis. After postnatal confirmation of the diagnosis, supportive care and conservative therapy were initiated. Six cases underwent mechanical ventilation, two were treated with surfactant and inhaled nitric oxide, four required inotropic support, and one underwent extracorporeal membrane oxygenation. Five newborns were effectively treated with octreotide. One patient with hydrops fetalis died after birth. Discussion: The prognosis of CC depends on the severity of the effusion and on associated abnormalities. Medical treatment is based on supportive and conservative treatment. Although the use of octreotide is not unanimous, it proved to be an effective and safe adjuvant therapy in these patients.